Pengaruh Kualitas Audit, Kekuatan Pendapatan, Komite Audit terhadap Nilai Perusahaan - Juli Supriyatno, Dwi Retno Setianingrum; Hendrani, Ai (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2024)
Company value offers investors a framework to evaluate investment choices. The goal of the purpose of this research is to examine the impact of audit quality, revenue strength, and audit committee about the matter value of enterprises operating in the fundamental industrial and chemical domains that are listed on the Indonesia Stock Exchange (BEI) from 2020 to 2022. This research paradigm employs a causal design using secondary data sources. The sampling technique used was purposive sampling, including a selection of 32 firms over a span of 3 years. This yielded a total of 96 samples, namely in the form of annual report data from companies operating in the basic industrial and chemical sectors over the period of 2020-2022. This study employs a quantitative methodology by doing statistical analyses on the data. It utilizes research analysis techniques such as descriptive statistical analysis tests, classical statistical hypothesis testing, and conducting hypothesis testing via the use of multiple linear regression method. The study results suggest that the variable of audit quality has a substantial significant and advantageous effect on the company's valuation. The earnings power and audit committee variables have no impact the value of a firm